2017
DOI: 10.1007/s00261-017-1163-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel contrast-injection protocol for high-resolution abdominal CT-angiography: vascular visualization improvement with vasodilator

Abstract: Abdominal CTA using NTG improved visualization of the abdominal peripheral vessels. This improved arterial view may be beneficial for preoperative evaluation of the arterial anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…These authors found that there was a statistically significant difference in cross-sectional area between the nitrate and non-nitrate group at 10 cm distal to the origin of the superior mesenteric artery (11.6 ± 8.6 and 8.3 ± 3.2 mm 2 , respectively) despite the absence of a significant difference at the origin (34.6 ± 10.8 and 34.0 ± 5.5 mm 2 , respectively). The result by Hoshika et al 18 indicated that vessel dilatation due to sublingual was greater in the abdominal peripheral arteries than in large arteries, which is similar to what we have observed in our study. Similar positive effects of sublingual GTN on CTA performed before prostate artery embolization, which could combat the difficult vascular anatomy of the prostate gland, have also been reported 28 …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These authors found that there was a statistically significant difference in cross-sectional area between the nitrate and non-nitrate group at 10 cm distal to the origin of the superior mesenteric artery (11.6 ± 8.6 and 8.3 ± 3.2 mm 2 , respectively) despite the absence of a significant difference at the origin (34.6 ± 10.8 and 34.0 ± 5.5 mm 2 , respectively). The result by Hoshika et al 18 indicated that vessel dilatation due to sublingual was greater in the abdominal peripheral arteries than in large arteries, which is similar to what we have observed in our study. Similar positive effects of sublingual GTN on CTA performed before prostate artery embolization, which could combat the difficult vascular anatomy of the prostate gland, have also been reported 28 …”
Section: Discussionsupporting
confidence: 93%
“…We could not find any study evaluating the role of sublingual nitrate in peripheral CTA. However, a study by Hoshika et al 18 demonstrated that using sublingual nitrate before abdominal CTA improved visualization of peripheral abdominal vessels. These authors found that there was a statistically significant difference in cross-sectional area between the nitrate and non-nitrate group at 10 cm distal to the origin of the superior mesenteric artery (11.6 ± 8.6 and 8.3 ± 3.2 mm 2 , respectively) despite the absence of a significant difference at the origin (34.6 ± 10.8 and 34.0 ± 5.5 mm 2 , respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The quantitative assessment was evaluated for 4 main coronary arteries which is LM, LCX, LAD and RCA. These assessment of image quality was determined by measuring 4 parameters which is signal intensity (SI), image noise, signal-to-noise ratio (SNR), and contrast-to-noise ratio (CNR) (Kojima et al 2017). The measurements were performed on axial image of coronary arteries by one reviewer (radiographer).…”
Section: Quantitative Analysismentioning
confidence: 99%